Topsy + Tim make a new friend - Adamson, Jean; Adamson, Gareth (London, Ladybird, 2003)
Topsy and Tim are delighted to learn that their disabled friend Jenny is going to join their class. Lots of the children have never seen anyone on a wheel chair before but Miss Terry explains all about it and the class soon discover that Jenny really is no different to them.